Winters restrict a climate change–driven butterfly range expansion despite rapid evolution of seasonal timing traits - Mats Ittonen; Matthew E. Nielsen; Isabelle Siemers; Magne Friberg; Karl Gotthard (Proceedings of the National Academy of Sciences, 2025)
Climate change pushes species toward higher latitudes and altitudes, but the proximate drivers of range expansions vary, and it is unclear whether evolution facilitates climate change–induced range changes. In a temporally replicated field experiment, we translocated wall brown butterflies ( Lasiommata megera ) descending from range interior and range margin populations to sites at 1) the range interior, 2) the range margin, and 3) beyond the current northern range edge. Thereby, we tested for local adaptation in seasonal timing and winter survival and evaluated to what extent local adaptation influences the ongoing, climate-driven range expansion. Almost all individuals from all populations entered diapause at an appropriate time, despite previously identified among-population variation in diapause induction thresholds. Caterpillars of northern descent, however, grew faster than those from southern populations at all field sites. This may be a countergradient adaptation to compensate for the short, northern growing seasons, but we found no evidence for prewinter body mass affecting winter survival. In fact, winter survival was low overall—extremely so at the beyond range site—regardless of population origin, indicating that the primary constraint to range expansion is an inability to adapt to winter conditions. Hence, although range-expanding wall browns show clear local evolution of two traits related to seasonal timing, these putative local adaptations likely do not contribute to range expansion, which is instead limited by winter survival. To predict future range changes, it will be important to distinguish between the traits that evolve during range expansion and those that set the range limit.